A comparison between the European Court of Justice, the International Court of Justice and the International Tribunal of the Law of the Sea Convention with special emphasis on jurisdiction and enforcement - Blum, Jan Burkhard (Institute of Marine and Environmental Law, 2024)
On May 9, 1950 Robert Schuman, the French Foreign Minister, announced his proposal to place the whole French and German steel production under a common High Authority which allowed other European countries the opportunity to participate. In his proposal he took care to provide for the establishment of a court of justice subjecting the new authority to judicial control. One year later, in April, 1951 the European Coal and Steel Treaty (ECSC) was signed in Paris creating the Court of Justice, which was intended to ensure that the new community was governed by democratic principles and the rule of law. Following this, the ratification debates took place in the parliaments of the six countries.